Family firms and family business: a conceptual approach about the ambiguities, paradoxes and uniqueness of family businesses - Rodrigues, Jorge (2019)
Family businesses are and have been vital in the European’s socioeconomic contexts. Notwithstanding their relevance and growing interest in academy, as well as in the institutional rationale, the study of family businesses is still a field that lacks autonomy and finds itself embedded in ambiguities, paradoxes and inconsistencies. This lack of systematisation not only compromises the process of data collection and research but consequently a better understanding of this phenomenon. Our purpose here is to discuss the constructs of family firm and family business. Based on the assumption that family firms are usually conceptualised as owned, totally or partially, by members of a family and are potentially intergenerational systems, with a perimeter of variable geometry, but usually rooted in a location, we aim to distinguish between the constructs of family firm and family business. We do this by discussing the concept(s) of family and then move on to the family businesses. Methodologically we carried out a literature analysis or review, based on Bourdieu’s (1972) “Theory of Practice”, understood as an approach that aims to overcome dichotomies in social theory, such as micro/macro, material/symbolic, empirical/theoretical, objective/subjective, public/private, structure/agency, and focuses on the understanding the practical logic of everyday life and understand relations of power. Enabling us to overcome the ambiguities and paradoxes that academically and institutionally surround the use of these constructs – family firms and family business. Our findings allowed us to sustain that the family business emerges as conceptual “leap forward”, i.e., the family firm becomes a family business when it becomes more strategically business-oriented. As an open system, the firm has a flow of inputs and outputs of members, which generate its unique configurations over time and potentiates intra and inter-clan conflicts and political and power struggles between family members and or among family members and their relatives and tends to create formal organisational structures (boards of directors) to assure its continuity and growth. In this context, when the above-mentioned criterion is met, the family business only exists from the second generation onwards.